Negative electrode sheet, method for manufacturing the same, and solid-state battery

CN123017886APending Publication Date: 2026-10-30BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610056160.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]有鉴于此,本申请提供一种负极极片及制备方法、固态电池,以至少解决现有技术中固态电池固-固界面易出现接触不良,影响电池的倍率性能与循环寿命的问题

Benefits of technology

本申请的负极极片包括负极集流体、活性物质层和固态电解质层;活性物质层设置于负极集流体的至少一个表面,固态电解质层设置于活性物质层的表面;其中,活性物质层中混合有电解质颗粒,电解质颗粒与固态电解质层中的电解质为相同体系材料。如此设置,分散的电解质颗粒能够连接活性物质层中活性材料的颗粒,形成贯穿活性物质层的三维离子通路,从而缩短离子的迁移距离,减小离子迁移阻力,提升离子传导效率,有效改善因固-固界面接触不良导致的离子传输受阻的问题,避免离子在负极侧的局部富集形成“孤岛效应”,从而改善固态电池的倍率性能与循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017886A_ABST
    Figure CN123017886A_ABST
Patent Text Reader

Abstract

The application provides a negative electrode sheet and a preparation method thereof, and a solid-state battery. The negative electrode sheet comprises a negative electrode current collector, an active material layer, and a solid-state electrolyte layer. The active material layer is arranged on at least one surface of the negative electrode current collector, and the solid-state electrolyte layer is arranged on a surface of the active material layer. The active material layer contains electrolyte particles, and the electrolyte particles and the electrolyte in the solid-state electrolyte layer are the same system material. In this way, the dispersed electrolyte particles can connect the active material particles in the active material layer, forming a three-dimensional ion channel through the active material layer, thereby shortening the ion migration distance, reducing the ion migration resistance, improving the ion conduction efficiency, effectively improving the problem of ion transmission obstruction caused by poor solid-solid interface contact, avoiding the local enrichment of ions on the negative electrode side to form an "island effect", and thus improving the rate performance and cycle life of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid-state battery technology, and in particular to a negative electrode sheet and its preparation method, and a solid-state battery. Background Technology

[0002] As market demand for battery energy density and safety performance continues to rise, solid-state batteries, with their core advantages of high energy density and high safety, are widely regarded as the core development direction for the next generation of power sources for new energy vehicles.

[0003] Solid-state batteries often use a fully solid-state interface contact for their negative electrode. However, during charge-discharge cycles, poor contact can easily occur at the solid-solid interface, leading to increased internal resistance and decreased ion conductivity. At the same time, ions tend to accumulate locally on the negative electrode side, ultimately causing accelerated degradation of the battery's rate performance and cycle life.

[0004] Therefore, solving the solid-solid interface contact problem in solid-state batteries has become a critical issue that urgently needs to be addressed in the current development of solid-state batteries. Summary of the Invention

[0005] In view of this, this application provides a negative electrode sheet and its preparation method, as well as a solid-state battery, to at least solve the problem in the prior art that poor contact easily occurs at the solid-solid interface of solid-state batteries, affecting the rate performance and cycle life of the battery.

[0006] To achieve the above objectives, the technical solution of this application is implemented as follows: This application provides a negative electrode sheet, including a negative electrode current collector, an active material layer, and a solid electrolyte layer; The active material layer is disposed on at least one surface of the negative electrode current collector, and the solid electrolyte layer is disposed on the surface of the active material layer; The active material layer contains electrolyte particles, and the electrolyte particles and the electrolyte in the solid electrolyte layer are made of the same material system.

[0007] Optionally, the electrolyte particles account for 15%-40% of the mass of the active material layer.

[0008] Optionally, the active material layer may also contain a conductive agent.

[0009] Optionally, the conductive agent accounts for 0.05%-3% of the mass of the active material layer.

[0010] Optionally, the conductive agent includes one or more of carbon nanotubes, carbon fibers, carbon nanofibers, and carbon microtubes.

[0011] Optionally, the active material in the active material layer is amorphous silicon and / or nano-silicon; and / or, the particle size of the active material in the active material layer is ≤2nm.

[0012] This application also provides a method for preparing a negative electrode sheet, the method comprising the following steps: Step S11: Add the active material and electrolyte particles to the first solvent and mix them evenly to obtain the first slurry; Step S12: The first slurry is coated onto the surface of the negative electrode current collector to form an active material layer; Step S13: Add the solid electrolyte to the second solvent and mix evenly to obtain the second slurry; wherein the solid electrolyte and the electrolyte particles are materials of the same system. Step S14: The second slurry is coated onto the surface of the active material layer to form a solid electrolyte layer, and the negative electrode sheet to be processed is obtained. Step S15: Dry the negative electrode sheet to be processed to obtain the finished negative electrode sheet.

[0013] Optionally, in step S11, the total mass ratio of the active material and the electrolyte particles to the mass ratio of the first solvent is 1:(1.5-3); and / or, in step S13, the mass ratio of the solid electrolyte to the second solvent is 1:(1.5-3).

[0014] Optionally, prior to step S11, the method further includes the following steps: Step S21: Heat the tubular furnace and introduce argon gas into the tubular furnace; Step S22: Introduce silane gas into the tubular furnace; Step S23: When the silane gas content in the tube furnace reaches a preset threshold, argon gas is introduced into the tube furnace, and the tube furnace is cooled to room temperature to obtain silicon-based active material.

[0015] This application also provides a solid-state battery, including a positive electrode, a solid electrolyte membrane, and a negative electrode as described in any of the preceding claims, wherein the positive electrode, the solid electrolyte membrane, and the negative electrode are stacked together.

[0016] Compared with the prior art, the negative electrode sheet described in this application has the following advantages: The negative electrode of this application includes a negative current collector, an active material layer, and a solid electrolyte layer. The active material layer is disposed on at least one surface of the negative current collector, and the solid electrolyte layer is disposed on the surface of the active material layer. The active material layer contains electrolyte particles, which are made of the same material system as the electrolyte in the solid electrolyte layer. This configuration allows the dispersed electrolyte particles to connect with the active material particles in the active material layer, forming a three-dimensional ion pathway that penetrates the active material layer. This shortens the ion migration distance, reduces ion migration resistance, and improves ion conduction efficiency. It effectively addresses the problem of ion transport obstruction caused by poor solid-solid interface contact, and avoids the formation of "island effects" due to localized ion accumulation on the negative electrode side, thereby improving the rate performance and cycle life of the solid-state battery. Attached Figure Description

[0017] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic diagram of the structure of a negative electrode sheet in an embodiment of this application.

[0018] Explanation of reference numerals in the attached figures: 10-Negative electrode current collector, 20-Active material layer, 201-Electrolyte particles, 202-Conductive agent, 30-Solid electrolyte layer. Detailed Implementation

[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0020] The terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and not to describe a specific order or sequence. It should be understood that such use of data can be interchanged where appropriate so that embodiments of this application can be implemented in orders other than those illustrated or described herein, and the objects distinguished by "first," "second," etc., are generally of the same class and the number of objects is not limited; for example, a first object can be one or more. Furthermore, in the specification and claims, "and / or" indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.

[0021] It should be understood that the phrase "some embodiments" throughout the specification means that a specific feature, structure, or characteristic related to an embodiment is included in at least one embodiment of this application. Therefore, "some embodiments" appearing throughout the specification does not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments.

[0022] The following detailed description of a negative electrode sheet and its preparation method, as well as a solid-state battery, provided in this application, is illustrated through specific embodiments.

[0023] In existing solid-state battery systems, during charge-discharge cycles, the solid-solid interface between the active material layer of the negative electrode and the solid electrolyte layer is prone to poor contact due to stress changes, volume expansion and contraction, and other factors. This problem directly leads to an increase in the battery's internal resistance and a sharp decline in the interfacial ion conductivity. At the same time, the migration path of ions on the negative electrode side is blocked, which easily leads to local enrichment and the generation of an "island effect," ultimately causing the battery's rate performance and cycle life to decline rapidly, which seriously restricts the development of solid-state batteries.

[0024] Based on this, the embodiments of this application provide a negative electrode sheet, referring to... Figure 1 The negative electrode sheet includes a negative current collector 10, an active material layer 20, and a solid electrolyte layer 30; the active material layer 20 is disposed on at least one surface of the negative current collector 10, and the solid electrolyte layer 30 is disposed on the surface of the active material layer 20; wherein, the active material layer 20 contains electrolyte particles 201, and the electrolyte particles 201 and the electrolyte in the solid electrolyte layer 30 are of the same material system.

[0025] Among them, the negative electrode current collector 10 can be a porous copper foil, and its surface is coated with a carbon nanotube coating after plasma etching treatment. In this way, on the one hand, the bonding strength between the negative electrode current collector 10 and the active material layer 20 can be improved, and on the other hand, the direct contact between the copper foil and the metal ions in the active material can be isolated, the formation of alloy can be suppressed, and the risk of interfacial side reactions can be reduced.

[0026] An active material layer 20 is disposed on at least one surface of the negative electrode current collector 10. For example, the active material layer 20 may be disposed on one surface of the negative electrode current collector 10 to form a single-sided coating structure, or it may be disposed on both surfaces of the negative electrode current collector 10 to form a double-sided coating structure. The active material layer 20 is made of an active material, which may be a silicon-based active material, such as one or more of nano-silicon, amorphous silicon, silicon oxide, and silicon carbide.

[0027] A solid electrolyte layer 30 is disposed on the surface of the active material layer 20 away from the current collector. The solid electrolyte layer 30 is a dense and continuous thin film structure. The electrolyte in the solid electrolyte layer 30 can be a sulfide electrolyte or an oxide electrolyte. Both types of electrolytes have high ionic conductivity and good chemical stability, which can effectively meet the working requirements of silicon-based active materials. Among them, the sulfide electrolyte uses sulfur as the core anionic framework, combined with cations such as lithium and boron. High ionic conductivity is achieved by controlling the element ratio, and it has excellent interfacial compatibility with silicon-based active materials, which can effectively suppress interfacial side reactions. The oxide electrolyte uses oxygen as the core anionic framework, combined with cations such as aluminum, titanium, and zirconium. It has good chemical stability and oxidation resistance, improving battery safety performance. The solid electrolyte layer 30 can serve as a transition layer between the active material layer 20 and the cell-level solid electrolyte film, reducing interfacial contact resistance. On the other hand, it can effectively block the penetration of active materials, improving battery safety performance.

[0028] The active material layer 20 contains electrolyte particles 201. These electrolyte particles 201 and the electrolyte in the solid electrolyte layer 30 are made of the same material system. Specifically, this means that the electrolyte particles 201 in the active material layer 20 and the electrolyte used in the solid electrolyte layer 30 belong to the same broad category, and their chemical structures and ion conduction mechanisms are consistent. However, this does not mean they have completely identical formulations or morphologies. For example, if the electrolyte in the solid electrolyte layer 30 is a sulfide electrolyte, then the active material layer 20 contains sulfide electrolyte particles 201; if the electrolyte in the solid electrolyte layer 30 is an oxide electrolyte, then the active material layer 20 contains oxide electrolyte particles 201. It should be noted that during the preparation process, the active material particles are mixed with micron- or nano-sized electrolyte particles 201 to ensure sufficient and uniform mixing of the active material and electrolyte particles 201. Using electrolytes of the same material system can reduce the interfacial impedance between the active material layer 20 and the solid electrolyte layer 30 caused by material differences, thereby improving the continuity and uniformity of ion conduction within the negative electrode.

[0029] The negative electrode sheet in this application embodiment can serve as the negative electrode structure of a solid-state battery. Taking a silicon-based negative electrode solid-state battery as an example, during the battery charging stage, lithium ions in the positive electrode sheet migrate to the negative electrode sheet through the cell-level solid electrolyte membrane between the positive and negative electrode sheets under the action of an electric field, and embed themselves in the lattice or pores of the silicon-based active material to form a lithium-silicon alloy. At this time, lithium ions exist in the negative electrode active material in an embedded state, while electrons flow from the positive electrode to the negative electrode through the external circuit to achieve charge balance. During the battery discharging stage, the lithium-silicon alloy in the negative electrode sheet undergoes a delithiation reaction, and lithium ions are extracted from the silicon-based active material and migrate back to the positive electrode through the cell-level solid electrolyte membrane between the positive and negative electrode sheets. Electrons flow to the positive electrode through the external circuit to form a current.

[0030] In this embodiment, electrolyte particles 201 are mixed in the active material layer 20, and the electrolyte particles 201 and the electrolyte in the solid electrolyte layer 30 are of the same material system. The dispersed electrolyte particles 201 can connect with the active material particles in the active material layer 20 to form a three-dimensional ion pathway that penetrates the active material layer 20, thereby shortening the migration distance of ions, reducing ion migration resistance, improving ion conduction efficiency, effectively improving the problem of ion transport obstruction caused by poor solid-solid interface contact, avoiding the formation of "island effect" by local enrichment of ions on the negative electrode side, thereby improving the rate performance and cycle life of solid-state batteries.

[0031] Optionally, in some embodiments of this application, the mass percentage of electrolyte particles 201 in the active material layer 20 is 15%-40%. For example, the mass percentage of electrolyte particles 201 in the active material layer 20 can be any one of 15%, 20%, 25%, 30%, 35%, and 40%. Within the above range, the larger the mass percentage of electrolyte particles 201 in the active material layer 20, the more fully the electrolyte particles 201 can fill the gaps between the active materials in the active material layer 20, forming high-density, continuous ion transport channels and significantly reducing ion migration resistance. Within the above range, the smaller the mass percentage of electrolyte particles 201 in the active material layer 20, the higher the proportion of active material. Since electrolyte particles 201 do not participate in electrochemical reactions and are considered "inactive components," a high proportion of active material can effectively ensure energy density and meet the design requirements of high-energy-density batteries.

[0032] Optionally, in some embodiments of this application, the active material layer 20 is further mixed with a conductive agent 202. The conductive agent 202 can be one or more of conductive carbon black, Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fibers, carbon nanotubes, or graphene. In this embodiment, a carbon-based conductive agent 202 with an aspect ratio >10 can be selected, such as carbon nanotubes, carbon fibers, carbon nanofibers, carbon microtubes, etc. Carbon nanotubes have an aspect ratio range of approximately 50-1000, possess extremely high electronic conductivity, excellent mechanical flexibility, and can form a highly efficient conductive pathway with a small amount added. Carbon fibers have an aspect ratio range of approximately 20-500, and their length and diameter can be controlled through the preparation process. Their mechanical strength is higher than that of carbon nanotubes, and they can simultaneously serve as conductors and electrode structure supports. Carbon nanofibers have an aspect ratio range of approximately 10-300, which can be precisely controlled to the target range. They have a large specific surface area, good interfacial compatibility with silicon particles and solid electrolytes, and can balance conductivity and bonding assistance. The aspect ratio of carbon microtubes ranges from approximately 10 to 100, and their production cost is low, which can effectively control the preparation cost of negative electrode sheets.

[0033] Mixing conductive agent 202 into the active material layer 20 enables the formation of a continuous three-dimensional electronic pathway between the active material and electrolyte particles 201, significantly reducing the internal resistance of electron transport and preventing battery rate performance degradation due to obstructed electron conduction. Simultaneously, conductive agent 202 fills the tiny gaps between the active material and electrolyte particles 201, increasing the density of the active material layer 20, reducing interfacial porosity, and improving battery cycle consistency.

[0034] Optionally, in some embodiments of this application, the mass percentage of conductive agent 202 in the active material layer 20 is 0.05%-3%. For example, the mass percentage of conductive agent 202 in the active material layer 20 can be any one of 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, and 0.3%. Within the above range, a higher mass percentage of conductive agent 202 in the active material layer 20 makes it easier to form a high-density, dead-angle-free electron transport network, reducing interfacial porosity. Within the above range, a lower mass percentage of conductive agent 202 in the active material layer 20 allows for more space to be released for the active material and electrolyte particles 201, improving the energy density of the battery.

[0035] Optionally, in some embodiments of this application, the active material in the active material layer 20 is amorphous silicon and / or nano-silicon. Amorphous silicon, also known as non-crystalline silicon, lacks a fixed crystal structure and a defined particle size. It can be prepared in thin films, powders, etc., and can be fabricated through methods such as vapor deposition, liquid-phase quenching, and high-energy ball milling. Amorphous silicon contains numerous defects and voids, which better facilitate ion insertion and extraction, resulting in low expansion and stronger interface stability. Furthermore, the disordered structure eliminates grain boundary barriers, reducing the migration resistance of lithium ions within the amorphous phase and thus improving ion conduction efficiency. Nano-silicon has a particle size in the nanometer range and can be prepared using vapor-phase condensation, chemical etching, or sol-gel methods. Nano-silicon has relatively high electronic conductivity, achieving efficient electron transport without requiring a large amount of conductive agent 202. Simultaneously, the high specific surface area of ​​the nanoparticles increases the contact sites with the solid electrolyte layer 30, reducing solid-solid interface impedance.

[0036] Optionally, in some embodiments of this application, the particle size of the active material in the active material layer 20 is ≤2nm. This effectively alleviates the problem of volume expansion of the active material layer 20 during battery charging and discharging, and improves the ion transport efficiency and cycle stability inside the electrode. For example, the active material can be any one or more of amorphous silicon, nano-silicon, and CVD (Chemical Vapor Deposition) silicon-carbon materials.

[0037] This application also provides a method for preparing a negative electrode sheet, which is used to prepare a negative electrode sheet as described in any of the foregoing claims. The method includes the following steps: Step S11: Add the active material and electrolyte particles 201 to the first solvent and mix them evenly to obtain the first slurry.

[0038] The active material is the main material of the active material layer 20, and can be a silicon-based active material, such as one or more of nano-silicon, amorphous silicon, silicon oxide, and silicon carbon. The electrolyte particles 201 are made of the same or similar materials as the electrolyte in the solid electrolyte layer 30. The first solvent can be xylene. Xylene has excellent surface compatibility with silicon-based active materials and carbon-based conductive agents 202, and can form an adsorption layer on the surface of the material particles, effectively preventing particle aggregation and flocculation. At the same time, xylene has no dissolving effect on sulfide and oxide solid electrolyte particles 201, which can effectively ensure the structural integrity of electrolyte particles 201 and maintain their ion conduction performance.

[0039] In this step, a certain amount of active material, electrolyte particles 201 and xylene solvent can be added to a mixing tank. The mixing tank is stirred at a speed of 2000 rpm to 3000 rpm for 80 s to 100 s to obtain the first slurry.

[0040] Step S12: The first slurry is coated onto the surface of the negative electrode current collector 10 to form an active material layer 20.

[0041] In this step, a coating device can be used to coat the first slurry onto at least one surface of the negative electrode current collector 10, forming an active material layer 20 on the surface of the negative electrode current collector 10. The negative electrode current collector 10 can be a porous copper foil.

[0042] Step S13: Add the solid electrolyte to the second solvent and mix evenly to obtain the second slurry; wherein the solid electrolyte and the electrolyte particles are materials of the same system.

[0043] In this process, the solid electrolyte and the electrolyte particles 201 in step S11 are the same or homologous materials. The second solvent can be the same as the first solvent. For example, xylene is also used as the second solvent. The same solvent system can ensure that the surface tension and wetting characteristics of the two slurries are highly matched, avoiding defects such as interlayer delamination and interface porosity caused by differences in solvent systems. At the same time, the same solvent will not change the surface properties of the silicon-based active material and electrolyte particles 201 in the active material layer 20, which is conducive to ensuring the continuous transport of ions between layers and reducing interfacial impedance.

[0044] In this step, solid electrolyte particles 201 and xylene solvent are added to a mixing tank, and the mixing tank is stirred at a speed of 2000 rpm to 3000 rpm for 80 s to 100 s to obtain the second slurry.

[0045] Step S14: The second slurry is coated onto the surface of the active material layer 20 to form a solid electrolyte layer 30, and the negative electrode sheet to be processed is obtained.

[0046] In this step, a scraping device can be used to scrape the second slurry onto the surface of the active material layer 20 away from the negative electrode current collector 10. The second slurry solidifies to form a solid electrolyte layer 30. The negative electrode current collector 10, the active material layer 20, and the solid electrolyte layer 30 are stacked in sequence to form the negative electrode sheet to be processed.

[0047] Step S15: Dry the negative electrode sheet to be processed to obtain the finished negative electrode sheet.

[0048] In this step, the negative electrode sheet to be processed is placed in an oven and baked at a temperature of about 60°C for 40-50 minutes to obtain the finished negative electrode sheet.

[0049] Optionally, in some embodiments of this application, in step S11, the mass ratio of the total mass of the active material and electrolyte particles 201 to the mass of the first solvent is 1:(1.5-3). For example, the mass ratio of the total mass of the active material and electrolyte particles 201 to the xylene solvent can be 1:2 to control the concentration of substances and the viscosity of the slurry, better adapting to the dispersion requirements of the silicon-based active material and electrolyte particles 201. Alternatively, in step S13, the mass ratio of the solid electrolyte to the second solvent is 1:(1.5-3). For example, the mass ratio of the solid electrolyte particles 201 to the xylene solvent can be 1:2 to control the concentration of substances and the viscosity of the slurry, better adapting to the dispersion requirements of the solid electrolyte particles 201. Of course, the method for preparing the negative electrode sheet of this application can simultaneously meet both of the above requirements to achieve better results.

[0050] Optionally, in some embodiments of this application, before step S11, the method for preparing the negative electrode sheet further includes the following steps: Step S21: Heat the tubular furnace and introduce argon gas into the tubular furnace.

[0051] In this step, the temperature inside the tube furnace can be raised to about 630℃-640℃, and argon gas can be introduced into the tube furnace to create an inert protective atmosphere, prevent the silicon-based material from oxidizing, and ensure the purity, structural integrity and performance stability of the material.

[0052] Step S22: Introduce silane gas into the tubular furnace.

[0053] In this step, silane gas can be introduced into the tube furnace for about 1 hour. Silane molecules have a simple structure and a high silicon content, and are prone to thermal decomposition under the high temperature environment of the tube furnace to generate elemental silicon atoms, which are eventually grown into the target silicon-based material.

[0054] Step S23: When the silane gas content in the tube furnace reaches a preset threshold, argon gas is introduced into the tube furnace, and the tube furnace is cooled to room temperature to obtain silicon-based active material.

[0055] In this step, after silicon atoms have completed nucleation and growth on the substrate surface, the silane gas is stopped, and high-purity argon gas is continuously introduced into the tube furnace to create an inert protective atmosphere. Then, the tube furnace is slowly cooled to room temperature. Once the temperature inside the furnace is consistent with the ambient temperature, the argon gas is stopped, and the furnace is opened to obtain the target silicon-based active material.

[0056] This application also provides a solid-state battery, including a positive electrode, a solid electrolyte membrane, and a negative electrode as described in any of the preceding claims, wherein the positive electrode, the solid electrolyte membrane, and the negative electrode are stacked together.

[0057] Specifically, the solid-state battery adopts a stacked sandwich structure, with the positive electrode, solid electrolyte membrane, and negative electrode tightly stacked from the inside out. The solid electrolyte membrane is a cell-level solid electrolyte membrane sandwiched between the positive and negative electrodes. Its material system is consistent with the solid electrolyte particles 201 mixed into the positive and negative electrodes, enabling efficient ion transport. Taking a silicon-based negative electrode solid-state battery as an example, during the charging phase, lithium ions in the positive electrode migrate to the negative electrode under the influence of an electric field through the cell-level solid electrolyte membrane and embed into the lattice or pores of the silicon-based active material, forming a lithium-silicon alloy. At this time, lithium ions exist in an embedded state in the negative electrode active material, while electrons flow from the positive electrode to the negative electrode through the external circuit, achieving charge balance. During the discharging phase, the lithium-silicon alloy in the negative electrode undergoes a delithiation reaction, and lithium ions are extracted from the silicon-based active material and migrate back to the positive electrode through the cell-level solid electrolyte membrane. Electrons flow to the positive electrode through the external circuit, forming a current.

[0058] The solid-state battery of this application embodiment uses the negative electrode sheet described in any of the preceding claims, and has the same or similar advantages as the negative electrode sheet: the active material layer 20 of the negative electrode sheet is mixed with electrolyte particles 201, and the electrolyte particles 201 and the electrolyte in the solid electrolyte layer 30 are of the same material system. With this configuration, the dispersed electrolyte particles 201 can connect with the active material particles in the active material layer 20, forming a three-dimensional ion pathway that penetrates the active material layer 20, thereby shortening the ion migration distance, reducing ion migration resistance, improving ion conduction efficiency, effectively improving the problem of ion transport obstruction caused by poor solid-solid interface contact, and avoiding the formation of an "island effect" due to local ion enrichment on the negative electrode side, thereby improving the rate performance and cycle life of the solid-state battery.

[0059] The present application will be described in detail below through embodiments.

[0060] Example 1 The active material in the active material layer is micron-crystalline silicon, and electrolyte particles are mixed into the active material layer. The electrolyte particles are made of the same material system as the electrolyte in the solid electrolyte layer. The electrolyte particles and micron-crystalline silicon are mixed in a ratio of 25% and 75% to prepare a negative electrode sheet, and finally a solid-state battery is prepared.

[0061] Example 2 The process of preparing the negative electrode sheet and solid-state battery in this embodiment is basically the same as that in Example 1. The only difference is that in this embodiment, a conductive agent is also mixed into the active material layer. The conductive agent is carbon fiber. Electrolyte particles, micron-sized silicon, and carbon fiber are mixed in a ratio of 25%, 72%, and 3% to prepare the negative electrode sheet, and finally to prepare the solid-state battery.

[0062] Example 3 The process of preparing the negative electrode sheet and solid-state battery in this embodiment is basically the same as that in Example 2. The only difference is that in this embodiment, electrolyte particles, micron-sized silicon, and carbon fibers are mixed in a ratio of 10%, 87%, and 3%, respectively.

[0063] Example 4 The process of preparing the negative electrode sheet and solid-state battery in this embodiment is basically the same as that in Example 2. The only difference is that in this embodiment, electrolyte particles, micron-sized silicon, and carbon fibers are mixed in a ratio of 45%, 52%, and 3%, respectively.

[0064] Example 5 The process of preparing the negative electrode sheet and solid-state battery in this embodiment is basically the same as that in Example 2. The only difference is that in this embodiment, the active material in the active material layer in Example 1 is adjusted to CVD silicon carbon, and the electrolyte particles, CVD silicon carbon and carbon fiber are mixed in a ratio of 25%:72%:3%.

[0065] Example 6 The process of preparing the negative electrode sheet and solid-state battery in this embodiment is basically the same as that in Example 2. The only difference is that in this embodiment, the active material in the active material layer in Example 1 is adjusted to amorphous elemental silicon, and the electrolyte particles, amorphous elemental silicon and carbon fiber are mixed in a ratio of 25%:72%:3%.

[0066] Example 7 The process of preparing the negative electrode sheet and solid-state battery in this embodiment is basically the same as that in Example 1. The only difference is that in this embodiment, a conductive agent is also mixed into the active material layer. The conductive agent is a single-walled carbon nanotube. The electrolyte particles, micron-sized crystalline silicon, and single-walled carbon nanotubes are mixed in a ratio of 25%, 74%, and 1%, respectively.

[0067] Example 8 The process of preparing the negative electrode and solid-state battery in this embodiment is basically the same as that in Example 7. The only difference is that in this embodiment, electrolyte particles, micron-sized crystalline silicon, and single-walled carbon nanotubes are mixed in a ratio of 25%:74.97%:0.03%.

[0068] Example 9 The process of preparing the negative electrode and solid-state battery in this embodiment is basically the same as that in Example 7. The only difference is that in this embodiment, electrolyte particles, micron-sized crystalline silicon, and single-walled carbon nanotubes are mixed in a ratio of 25%:70%:5%.

[0069] Comparative Example 1 The difference between this embodiment and Embodiment 1 is that the active material layer does not contain electrolyte particles or conductive agents; the active material layer only contains micron-sized crystalline silicon, thereby preparing a negative electrode sheet and ultimately preparing a solid-state battery.

[0070] The solid-state batteries obtained in each embodiment and comparative example were subjected to cycle capability tests, and the results are shown in Table 1.

[0071] Table 1

[0072] As shown in Table 1, the solid-state battery in Comparative Example 1, without electrolyte particles and conductive agents mixed in the active material layer, exhibited weak cycle life, only reaching 150 cycles. In Example 1, mixing electrolyte particles in the active material layer improved the cycle life of the solid-state battery, allowing for 187 cycles. In Examples 2-9, mixing electrolyte particles and conductive agents in the active material layer significantly enhanced the cycle life of the solid-state battery. Therefore, mixing electrolyte particles and conductive agents in the active material layer effectively improves the problem of ion transport obstruction caused by poor solid-solid interface contact, thereby improving the rate performance and cycle life of solid-state batteries.

[0073] Finally, it should be noted that the term "comprising" or any other variations thereof in the specification and claims of this application is intended to cover a non-exclusive inclusion, such that a process, method, article, or terminal device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or terminal device. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or terminal device that includes said element.

[0074] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A negative electrode sheet, characterized in that, It includes a negative electrode current collector, an active material layer, and a solid electrolyte layer; The active material layer is disposed on at least one surface of the negative electrode current collector, and the solid electrolyte layer is disposed on the surface of the active material layer; The active material layer contains electrolyte particles, and the electrolyte particles and the electrolyte in the solid electrolyte layer are made of the same material system.

2. The negative electrode sheet according to claim 1, characterized in that, In the active material layer, the electrolyte particles account for 15%-40% by mass.

3. The negative electrode sheet according to claim 1 or 2, characterized in that, The active material layer also contains a conductive agent.

4. The negative electrode sheet according to claim 3, characterized in that, In the active material layer, the conductive agent accounts for 0.05%-3% by mass.

5. The negative electrode sheet according to claim 3 or 4, characterized in that, The conductive agent includes one or more of carbon nanotubes, carbon fibers, carbon nanofibers, and carbon microtubes.

6. The negative electrode sheet according to any one of claims 1-5, characterized in that, The active material in the active material layer is amorphous silicon and / or nano-silicon; and / or, the particle size of the active material in the active material layer is ≤2nm.

7. A method for preparing a negative electrode sheet, characterized in that, The method includes the following steps: Step S11: Add the active material and electrolyte particles to the first solvent and mix them evenly to obtain the first slurry; Step S12: The first slurry is coated onto the surface of the negative electrode current collector to form an active material layer; Step S13: Add the solid electrolyte to the second solvent and mix evenly to obtain the second slurry; wherein the solid electrolyte and the electrolyte particles are materials of the same system. Step S14: The second slurry is coated onto the surface of the active material layer to form a solid electrolyte layer, and the negative electrode sheet to be processed is obtained. Step S15: Dry the negative electrode sheet to be processed to obtain the finished negative electrode sheet.

8. The method for preparing the negative electrode sheet according to claim 7, characterized in that, In step S11, the total mass of the active material and the electrolyte particles is in a mass ratio of 1:(1.5~3) to the mass of the first solvent. And / or, in step S13, the mass ratio of the solid electrolyte to the second solvent is 1:(1.5~3).

9. The method for preparing the negative electrode sheet according to claim 7, characterized in that, Prior to step S11, the method further includes the following steps: Step S21: Heat the tubular furnace and introduce argon gas into the tubular furnace; Step S22: Introduce silane gas into the tubular furnace; Step S23: When the silane gas content in the tube furnace reaches a preset threshold, argon gas is introduced into the tube furnace, and the tube furnace is cooled to room temperature to obtain silicon-based active material.

10. A solid-state battery, characterized in that, It includes a positive electrode, a solid electrolyte membrane, and a negative electrode as described in any one of claims 1-6, wherein the positive electrode, the solid electrolyte membrane, and the negative electrode are stacked together.